Flux Variations and Torque Reversals of Cen X-3 - Jiren Liu (The Astrophysical Journal)
Cen X-3 is an archetypical X-ray pulsar with strong flux variations and alternating torque reversals, both of which are similar to those of recently discovered pulsating ultraluminous X-ray sources. We study a low state of Cen X-3 that occurred in 2023, lasting for ∼100 days, with Chandra and Insight-HXMT observations, supplemented with MAXI and Fermi Gamma-ray Burst Monitor data. The Chandra spectrum during the eclipse of Cen X-3 in the low state is very similar to that in the high state, especially the Fe lines. The HXMT spectrum in the low state shows an enhanced Fe line, as do the MAXI data. The spin-up/spin-down trends of Cen X-3 are not affected by the low states. All these results indicate that the intrinsic emission in the low states is high, and the low states are just apparently low and are dominated by reprocessed emission. We found that the spin-up to spin-down reversals of Cen X-3 take a longer time than the spin-down to spin-up reversals, which provides a definite observation test of any possible torque-reversal models. We discuss insights from these results for understanding the pulsating ultraluminous X-ray sources.